Nifedipine Inhibition of High-Voltage Activated Calcium Channel Currents in Cerebral Artery Myocytes Is Influenced by Extracellular Divalent Cations - Wang, Fei; Koide, Masayo; Wellman, George C. (Frontiers in Physiology, 2017)
Voltage-dependent calcium channels (VDCCs) play an essential role in regulating cerebral artery diameter and it is widely appreciated that the L-type VDCC, CaV1.2, encoded by the CACNA1C gene, is a principal Ca2+ entry pathway in vascular myocytes. However, electrophysiological studies using 10 mM extracellular barium ([Ba2+]o) as a charge carrier have shown that approximately 20 % of VDCC currents in cerebral artery myocytes are insensitive to 1,4-dihydropyridine (1,4-DHP) L-type VDDC inhibitors such as nifedipine. Here, we investigated the hypothesis that the concentration of extracellular divalent cations can influence nifedipine inhibition of VDCC currents. Whole-cell VDCC membrane currents were obtained from freshly isolated rat cerebral artery myocytes in extracellular solutions containing Ba2+ and/or Ca2+. In the absence of [Ca2+]o, both nifedipine-sensitive and -insensitive calcium currents were observed in 10 mM [Ba2+]o. However, VDCC currents were abolished by nifedipine when using a combination of 10 mM [Ba2+]o and 100 µM [Ca2+]o. VDCC currents were also completely inhibited by nifedipine in either 2 mM [Ba2+]o or 2 mM [Ca2+]o. The biophysical characteristics of all recorded VDCC currents were consistent with properties of a high-voltage activated VDCC, such as CaV1.2. Further, VDCC currents recorded in 10 mM [Ba2+]o ± 100 µM [Ca2+]o or 2 mM [Ba2+]o exhibited similar sensitivity to the benzothiazepine L-type VDCC blocker, diltiazem, with complete current inhibit at 100 µM. These data suggest that nifedipine inhibition is influenced by both Ca2+ binding to an external site(s) on these channels and surface charge effects related to extracellular divalent cations. In sum, this work demonstrates that the extracellular environment can profoundly impact VDCC current measurements.